Room-temperature synthesis of blue-emissive zero-dimensional cesium indium halide quantum dots for temperature-stable down-conversion white light-emitting diodes with a half-lifetime of 186 h. Issue 12 (26th October 2021) - Zhang, Fei; Ji, Xinzhen; Liang, Wenqing; Li, Ying; Ma, Zhuangzhuang; Wang, Meng; Wang, Yue; Wu, Di; Chen, Xu; Yang, Dongwen; Li, Xinjian; Shan, Chongxin; et al.
Abstract : Zero-dimensional Cs3 InX6 QDs with broadband blue emission were synthesized at room-temperature. A white LED was further fabricated by using Cs3 InX6 QDs powder as down-conversion phosphor, demonstrating a remarkable working stability. Abstract : Recently, the newly-emerging lead halide perovskite quantum dots (QDs) have attracted intensive research interest for lighting and display applications owing to their remarkable optoelectronic properties. It is regrettable that the toxicity and instability of lead largely hinder their practical applications. Here, zero-dimensional (0D) cesium indium halide (Cs3 InX6 ) QDs were synthesized for the first time using a modified ligand-assisted reprecipitation method, and the emission wavelength can be tuned facilely via an anion exchange reaction. Typically, the Cs3 InBr6 QDs showed broadband blue emission with a high photoluminescence (PL) quantum yield of 46%. First-principles calculations were performed and temperature-dependent PL was studied to investigate the emission mechanisms of the Cs3 InBr6 QDs; the 0D nature of Cs3 InBr6 enhances the localization of excitons, resulting in a large exciton binding energy. It is worth noting that the strong electron–phonon coupling of Cs3 InBr6 indicates that the broadband emission comes from self-trapped exciton emission. Moreover, the Cs3 InX6 QDs exhibit excellent stability against moisture, ultraviolet light and heat degradation, significantly better than for conventional lead halide perovskites. Subsequently, the white light-emitting diodes (WLEDs) prepared using blue-emissive Cs3 InBr6 QD powder used as the phosphor showed an excellent working stability with a record half-life ( T 50 ) of 186 h. Even if the operating temperature is as high as 106.9 °C, the LED can still operate well and reach a T 50 of 50 h. These results highlight the huge advantages and application potential of 0D Cs3 InX6 QDs as an environmentally friendly emitter in the field of solid-state lighting.